Volar Distal Radioulnar Joint Dislocation Associated with Acute Median Nerve Neuropathy and a Distal Radius Fracture - Naser Alnusif; Sultan Aldebeyan; Rudolf Reindl (Case Reports in Orthopedics)
Volar distal radioulnar (DRUJ) dislocations are uncommon and can easily be missed. We present a rare case of an irreducible volar DRUJ dislocation associated with a distal radius fracture and acute median nerve neuropathy at the wrist. An attempt to reduce the DRUJ dislocation in the emergency department had failed. The patient was then taken to the operating room requiring a carpal tunnel release, as well as an open reduction and internal fixation of the distal radius fracture and repair of the volar distal radioulnar ligament. We also review some of the volar DRUJ case reports in the literature.